(3TQM bUjOI GdfGHZI GdPHjGfi (B( (3GdOGdjg (B)s - (3CHi GdMSf Ydj Hf CMeO Hf eMeO Hf Ydj Hf eJhjg GdhGMOi GdfjSCHhQis; (3RjGO Hf eYGhjI Hf VHGH GdPHjGfqj GdZWaGfqj GdeVQj, CHh CeGeI (B((3GdnqfGHnZI GdoqPrHnjGfj(B)s
(3ChdgG (B:s
(3jGOGQ ejg HGdYdjGA aGdSfO CbhJ aWGd YdjgG SGda GdCHO s
(3BNQgG (B:s
(3gPG GdPi PcQJ YRQi aEf de jfaYfi JMjQJ hde CgJOdhLgg JeJ GdbUjOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3fJab ai ChdgG hBNQgG eY GdfSNI GdChdis
(3HGNJdGa ai HYV GdCdaGXs
(3fSNI KGdKg s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs